2017
DOI: 10.1287/mnsc.2016.2426
|View full text |Cite
|
Sign up to set email alerts
|

When the Meaning of Work Has Disappeared: Experimental Evidence on Employees’ Performance and Emotions

Abstract: This experiment tests for a causal relationship between the meaning of work and employees' motivation to perform weil. The study builds on an existing employeremployee relationship, adding realism to the ongoing research of task meaning. Owing to an unexpected project cancelation, we are able to study how varying the information provided about the meaning of previously conducted work-without the use of deception, but still maintaining a high level of conh•ol-affects subsequent performance. We observe a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
(26 reference statements)
1
43
1
1
Order By: Relevance
“…When a work project terminated unexpectedly, all the workers' prior efforts suddenly became futile and the meaning of work disappeared. As a consequence, the workers were found to exert less effort in subsequent work tasks (Chadi et al, 2017). To conclude, a cross-task spillover effect was observed.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…When a work project terminated unexpectedly, all the workers' prior efforts suddenly became futile and the meaning of work disappeared. As a consequence, the workers were found to exert less effort in subsequent work tasks (Chadi et al, 2017). To conclude, a cross-task spillover effect was observed.…”
Section: Introductionmentioning
confidence: 74%
“…A growing body of literature has examined the antecedents and outcome variables of meaningful work in experimental settings (Ariely and Kamenica, 2008;Grant, 2008;Bäker and Mechtel, 2013;Chandler and Kapelner, 2013;Chadi et al, 2017;Kosfeld et al, 2017;Allan et al, 2018), and it was consistently found to be beneficial, both to the individuals and to the organization. Then, what if the meaning of work suddenly disappears?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research shows that the level of meaning of work is an important factor that impacts agents' effort levels and, thus, outputs. Scholars find that higher levels of task meaning are accompanied by higher output levels (Ariely, Kamenica, & Prelec, ; Chadi, Jeworrek, & Mertins, ; Chandler & Kapelner, ; Kosfeld, Neckermann, & Yang, ). However, in organizational practice, many tasks are characterized by a rather low task meaning, for example, due to a high degree of specialization and functional segmentation (e.g., Beugelsdijk, Pedersen, & Petersen, for a trend towards a more specialized and advanced global value chain configuration, yielding to more vertical specialization).…”
Section: Introductionmentioning
confidence: 99%